2009
DOI: 10.1007/s10152-009-0162-y
|View full text |Cite
|
Sign up to set email alerts
|

Copepod feeding study in the upper layer of the tropical South China Sea

Abstract: The South China Sea (SCS) is the world's largest marginal sea being notable for vertical mixing at various scales resulting in a sequence of chemical and biological dynamics in surface waters. We investigated the ingestion, gut content, evacuation and clearance rates of copepods collected from six stations (including a South East Asia Time Series station) along a transect line in the tropical of a SCS cruise during September 27, 1999 to October 2, 1999. The goal of the present study was to understand the feedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 46 publications
1
9
1
Order By: Relevance
“…Compared with previous studies in the northern South China Sea, the number of identified species is close to that recorded by Tseng et al (2009) who found 33 species from their feeding studies, being lower than that recorded by Tseng et al (2008a) who found 78 species in December and Hwang et al (2007) who found 101 species in October. A higher number of copepod species is recorded with respect to extended sampling area and sampling depth.…”
Section: Effects Of Monsoon and Seasonal Successioncontrasting
confidence: 48%
See 1 more Smart Citation
“…Compared with previous studies in the northern South China Sea, the number of identified species is close to that recorded by Tseng et al (2009) who found 33 species from their feeding studies, being lower than that recorded by Tseng et al (2008a) who found 78 species in December and Hwang et al (2007) who found 101 species in October. A higher number of copepod species is recorded with respect to extended sampling area and sampling depth.…”
Section: Effects Of Monsoon and Seasonal Successioncontrasting
confidence: 48%
“…Zooplankton has a great impact on the transfer of energy and nutrients throughout the food web (Turner 2004;Tseng et al 2008dTseng et al , 2009Hwang and Martens 2011). Different zooplankton taxa play different roles with different impacts.…”
Section: Introductionmentioning
confidence: 99%
“…Before the start of the experiment, the copepods were transferred from the stock culture to the new culture water for a 24‐hr gut evacuation to avoid the effects of resident algal diet (Tseng, Dahms, Chen, & Hwang, ). At the beginning of the experiment, eight ovigerous females were cultured in each replicate beaker with 400 ml of diluted seawater (20 gL −1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Metazooplankton including copepods, cladocerans, chaetognaths, larvae of invertebrates, and hydrozoans are a major component of the marine ecosystem (Fulton 1984, Kang et al 1996, Uye and Liang 1998, Calbet 2001, Gallienne and Robins 2001, Puelles et al 2003, Kimmel and Roman 2004, Turner 2004, Tseng et al 2009. They are consumers of phytoplankton and heterotrophic protists and are in turn prey for larval fish and other metazoans (Porter et al 1985, Houde and Roman 1987, Turner et al 1988, Stoecker and Capuzzo 1990, Sanders and Wickham 1993, Carlsson et al 1995, Croll et al 2005, Jeong et al 2007, Waggett et al 2008, Lazareva and Kopylov 2011.…”
Section: Introductionmentioning
confidence: 99%